137 A meta-analysis assessing the outcome of occupational injury by minority employee race. (5th May 2020) - Hicks, Chelsea; Kibibi, Niclette; Thomson, William
Abstract : Statement of Purpose: Literature suggests that racial disparities in the prevalence of occupational injury exist, but the magnitude of these disparities has not been summarized or well-described. The purpose of this meta-analysis was to examine differences of experienced workplace injury between White and Black employees. Methods: Our study population of interest was employees, teens to adults, who identified as non-Hispanic Black or non-Hispanic white, and who experienced an unintentional injury in the workplace. PubMed and Embase were searched, which resulted in a total of 488 published articles. Articles were identified and reviewed using search terms related to workplace injuries and racial ethnic disparities. Standard meta-analysis tools were used to rate the quality of the studies and data combined using generic inverse variance pooling. Random effects models were used to account for the heterogeneity between the studies. Results: A total of 5 articles met eligibility criteria and included workplace injury information from both national databases and smaller assessments. Publication dates ranged from 2003 to 2017 with cross sectional and cohort studies present. When assessing the outcome of injury for those who are a racial/ethnic minority, individuals who were African American were almost 2 times more likely to experience occupational injury than the White comparison group (pooled RR: 1.79, 95% CI 1.65 to 1.93). Conclusions: Differences in race increase the risk of experiencing workplace injuries. The causes of these discrepancies could vary greatly by occupation type. Future studies should summarize injury rates by occupation to allow for understanding of risks minority employees face. Significance and Contributions to Injury and Violence Prevention Science: It is important to understand the risks associated with injuries within the workplace that are making occupational environments less safe for minority workers. Understanding these risks allow for the development of innovative preventative methods to ensure all workers safe working environments.